A Review of the Synthesis of Quaternary Acetylcholinesterase Reactivators - Malinak, David; Korabecny, Jan; Soukup, Ondrej; Gorecki, Lukas; Nepovimova, Eugenie; Psotka, Miroslav; Dolezal, Rafael; Nguyen, Thuy D.; Mezeiova, Eva; Musilek, Kamil; Kuca, Kamil (Current Organic Chemistry, 2018)
Acetylcholinesterase (AChE) is well-known enzyme studied in many fields of research, e.g. in Alzheimer's disease, Parkinson's disease, or in eco-toxicology as a biological marker. Many inhibitors of AChE have been identified in nature as well as prepared in chemical labs as a result of systematic synthetic efforts. The organophosphorus (OP) inhibitors of AChE are one of the oldest artificial inhibitors being purposely developed as military nerve agents (e.g. sarin, soman, tabun, VX, RVX). Some of the compounds with decreased toxicity are currently used in agriculture as pesticides (e.g. parathion, chlorpyrifos, paraoxon) or in the industry as softening agents and flame retardants. The common mechanism of action of all organophosphate compounds is the irreversible inhibition of AChE via a binding to the hydroxyl group of the serine residue within the active site of the enzyme. Subsequently, AChE loses its ability to fulfill its physiological role in cholinergic transmission, which leads to the cholinergic crisis with the possibility of respiratory failure and death. The reactivators of AChE are classified as strong nucleophilic agents capable to cleave the non-aged organophosphate- serine adduct and thereby restoring the activity of the enzyme. This work provides a unique overview of the most potent oximes reactivators of inhibited AChE since 1955 to the present. In this review article, we have reviewed different synthetic approaches of known and widely used oxime reactivators of AChE such as pralidoxime, methoxime, trimedoxime, obidoxime, asoxime (HI-6), HS-6, HLo-7, K027, K048, K203, K075 and BI-6. The review covers the original articles as well as patented research.
Keywords: organophosphate